Women and Marriage in German Medieval Romance - Green, D. H (Cambridge University, 2013)
This book is conceived as a companion volume to Women Readers in the Middle Ages (Cambridge 2007), but with a double change of focus. In the earlier book I attempted to give a selective survey of the various classes of women in three countries (Germany, France, England) throughout the Middle Ages who were active as readers or engaged in other ways in literature, and also of the kinds of text they read, whereas now my question is more what appeals their reading made to them and how they may conceivably have reacted to it. Whereas the first book ranged over the whole span of the Middle Ages, from the seventh to the early sixteenth century, this one concentrates on the years before and immediately after 1200, above all because the wonderfully innovative force of the twelfth century promises illumination in regard to our question and because of the disturbances in the gender system which have been registered in that century. Focusing on the earliest German romances has the added advantage that they were written by authors of the highest rank and can be compared with French counterparts of similar quality.